2019
DOI: 10.32406/v2n32019/62-75/agrariacad
|View full text |Cite
|
Sign up to set email alerts
|

Germinação e avaliação morfológica de plântulas de pimentas (Capsicum spp.) cultivadas in vitro

Abstract: /agrariacad Germinação e avaliação morfológica de plântulas de pimentas (Capsicum spp.) cultivadas in vitro. Germination and morphological evaluation of peppers (Capsicum spp.) cultivated in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The pepper germplasm needs to be conserved to conduct any breeding project. Several studies have shown that the peppers in Brazil have a high genetic diversity (Carvalho et al, 2003;Ribeiro et al, 2008;Heinrich et al, 2015;Cardoso et al, 2018;Fernandes;Gomes;Nogueira, 2019;De Jesus et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pepper germplasm needs to be conserved to conduct any breeding project. Several studies have shown that the peppers in Brazil have a high genetic diversity (Carvalho et al, 2003;Ribeiro et al, 2008;Heinrich et al, 2015;Cardoso et al, 2018;Fernandes;Gomes;Nogueira, 2019;De Jesus et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The attributes of fruits and seeds obtained based on internationally presented descriptors (IPGRI, 1995) can help assess the genetic diversity of the species (Neitzke et al, 2014;Bernardo et al, 2018;Fernandes;Gomes;Nogueira, 2019). In this type of study, multivariate analyses complement traditional approaches and enhance the accuracy of data interpretation (Zago et al, 2017;Cardoso et al, 2018).…”
Section: Introductionmentioning
confidence: 99%